2021
DOI: 10.3892/ol.2021.12684
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of uPA and uPAR expression in patients with cervical cancer undergoing radiotherapy

Abstract: Cervical cancer remains a major health threat. Urokinase serves as a marker of metastatic tumors. The present study aimed to determine whether the expression levels of urokinase plasminogen activator (uPA) and urokinase plasminogen activator receptor (uPAR), before and during the course of radiotherapy, serve as prognostic markers for patients with cervical cancer. Cervical tumor tissue biopsies were collected from 72 patients before radiotherapy and after the completion of external beam radiotherapy (EBRT) be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
(55 reference statements)
2
5
0
Order By: Relevance
“…Regarding treatment stratification, clinicians need a tumor specific pre-treatment biomarker to predict the risk of recurrence. However, in our study pre-treatment total plasma uPAR was not able to predict RFS, in line with the results of previous studies, and a post-treatment sample is irrelevant for selecting therapy 8 . In contrast, we have previously shown that uPAR-PET/CT predicted RFS in a similarly sized study (n = 54) 17 .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Regarding treatment stratification, clinicians need a tumor specific pre-treatment biomarker to predict the risk of recurrence. However, in our study pre-treatment total plasma uPAR was not able to predict RFS, in line with the results of previous studies, and a post-treatment sample is irrelevant for selecting therapy 8 . In contrast, we have previously shown that uPAR-PET/CT predicted RFS in a similarly sized study (n = 54) 17 .…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, an increase in uPAR expression has been documented by other studies, e.g. a study analyzing plasma samples from esophageal cancer patients undergoing radiotherapy and a study on tissue samples collected from p16-positive cervical cancer patients also undergoing radiotherapy 7,8 . In contrast, a small study on HNSCC patients showed a reduction in plasma uPAR (n = 11), but the patients were referred to surgery and the timing of the samples were varying (1-42 days post-treatment) 13 .…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Further, elevated tumor uPA levels have been associated with a worse outcome or more advanced disease for all of these cancers (13)(14)(15)(16)(17)(18)(21)(22)(23). Also, plasma levels of uPA have been shown to be significantly elevated in patients with ovarian, endometrial, non-small cell lung cancer (NSCLC), gastric, hepatocellular, pancreatic, colorectal, and bladder cancers (24)(25)(26)(27)(28).…”
Section: What Is the Implication And What Should Change Now?mentioning
confidence: 99%